2024
DOI: 10.1177/19417381231223560
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Psychosocial Factors on Patients Undergoing Anterior Cruciate Ligament Reconstruction

Amit M. Momaya,
Audria S. Wood,
Elizabeth M. Benson
et al.

Abstract: Context: Anterior cruciate ligament (ACL) injuries greatly impact patients in terms of future performance, reduced physical activity and athletic participation, and overall economic burden. Decades of research have investigated how to improve ACL reconstruction (ACLR) outcomes. Recently, there has been growing interest to understand the effects of psychosocial factors on patient outcomes. Study Design: Clinical review. Evidence Acquisition: A search of the PubMed database was performed in March 2023. Articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 80 publications
(179 reference statements)
0
0
0
Order By: Relevance
“…Conversely, the most common reasons for not returning were lack of confidence in the knee and fear of reinjury. These factors are comparable to those identified in other reviews (Longo et al, 2023;Momaya et al, 2024;Nwachukwu et al, 2019). For example, Nwachukwu et al (2019) reported the most common reasons were fear of reinjury, lack of confidence in the knee, depression, and lack of interest or motivation.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Conversely, the most common reasons for not returning were lack of confidence in the knee and fear of reinjury. These factors are comparable to those identified in other reviews (Longo et al, 2023;Momaya et al, 2024;Nwachukwu et al, 2019). For example, Nwachukwu et al (2019) reported the most common reasons were fear of reinjury, lack of confidence in the knee, depression, and lack of interest or motivation.…”
Section: Discussionsupporting
confidence: 86%
“…For example, Nwachukwu et al (2019) reported the most common reasons were fear of reinjury, lack of confidence in the knee, depression, and lack of interest or motivation. Momaya et al (2024) identified motivation to return, lower levels of kinesiophobia, higher levels of self-efficacy, confidence and subjective knee function, risk acceptance and social support as factors that might predict athletes more likely to RTP. In contrast to previous reviews, personality factors as "adventure seeking" and "personal standards" related to RTP were found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations